2014
DOI: 10.1155/2014/291586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral PUVAsol on the Quality of Life in Indian Patients Having Chronic Plaque Psoriasis

Abstract: Background. Psoriasis is associated with a high impact on health-related QoL (quality of life). PUVAsol has been successfully used for treating psoriasis instead of standard PUVA therapy in developing countries. However, data for PUVAsol therapy and its effect on QoL in psoriatic patients is meagre. Objective. To investigate the effect of PUVAsol on the quality of life in patients having chronic plaque psoriasis. Materials and Methods. An observational prospective study done in patients having chronic plaque p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…6 Baseline DLQI scores are indicative of moderate QoL impairments associated with the disease, similar to those reported by other researchers. 5,16,[19][20][21] Phototherapy led to a significant decrease of DLQI score for 'symptoms and feelings' and 'treatment' subgroup that corresponds to results reported by other authors. 21 The QoL affection in the 'treatment' domain is expected since psoriasis is a chronic course skin disease that requires long-term management.…”
Section: Discussionsupporting
confidence: 88%
“…6 Baseline DLQI scores are indicative of moderate QoL impairments associated with the disease, similar to those reported by other researchers. 5,16,[19][20][21] Phototherapy led to a significant decrease of DLQI score for 'symptoms and feelings' and 'treatment' subgroup that corresponds to results reported by other authors. 21 The QoL affection in the 'treatment' domain is expected since psoriasis is a chronic course skin disease that requires long-term management.…”
Section: Discussionsupporting
confidence: 88%
“…Of these, PUVA (as bath or as systemic PUVA) 10 and PUVA sol have been used successfully in the treatment of psoriasis for more 40 yr, with PUVA sol being twice as cost-effective as PUVA 8 . Gahalaut et al 11 in a PP analysis of 40 patients of psoriasis treated with PUVA sol observed that 20 per cent of their patients achieved PASI 75, 40 per cent achieved PASI 50, while 10 per cent had an aggravation of their disease at 12 wk. The response of psoriasis to PUVA sol is enhanced by the concomitant use of retinoids 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Side effects are frequent with psoralen-based therapies. Gahalaut et al 11 and Aggarwal et al 8 reported that 60-70 per cent of their patients on PUVA developed side effects with more than half of these being nausea and vomiting. Parrish et al 19 and Singh et al 6 also reported 23 and 55.6 per cent of their patients on PUVA, respectively, complained of nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study between PUVA versus PUVAsol among patients with vitiligo indicated that PUVA is more efficacious and also provides a greater psychological benefit than PUVAsol. 9 Nevertheless the phototoxic side effects were found to be significantly greater among patients treated with PUVA therapy. However; lack of definite controlled parameters, noncompliance, privacy issues are some of its disadvantages.…”
Section: Short Communicationmentioning
confidence: 97%
“…9 Subsequent exposure until maximum of 30 minutes was reached. Similarly, Sornakumar L et al suggested turban PUVAsol at 5 minutes per exposure up to maximum of 15 minutes.…”
Section: Short Communicationmentioning
confidence: 99%